Investigation on Hadiths in al-Bayân al-Mulamma’ ‘an Alfâẕ al-Lam’ Written by Sahal Mahfudz | الاطلاع على أحاديث ((البيان الملمع عن ألفاظ اللمع)) للشيخ محمد أحمد سهل بن محفوظ الحاجيني - Ulin Nuha (Al-Zahra : Journal for Islamic and Arabic Studies, 2019)
The book of al-Bayân al-Mulamma’ ‘an Alfâẕ al-Lam’ written by Sahal Mahfudz, one of the Nusantara’s Ulama, is the comments of the Imam Syairozi’s book, al-Lam’ fî Uṣûl al-Fiqh. In Sahal’s book, there is a number of hadith without mentioning conductors of takhrij (hadith extraction and authentication in the collections). Based on this, the activity of takhrij is an important matter.The study uses the method of the forefathers in the takhrij activity of the hadiths in this book, such as Ibn Kathir in Tuḥfah al-Ṯâlib bi Ma’rifah Aḥâdîts Mukhtaṣar Ibn al-Ḥâjib, and Ibnu Hajar in Muwâfaqah al-Khabar fî Takhrîj Aḥâdîts al-Mukhtaṣar, and Abdullah ibn Muhammad Al-Ghamari in Takhrîj Aḥâdîts al-Lam’. After tracking the hadiths from the original sources then ruled by former ulama’s rule. If a contradiction is found, tarjih will be applied.The findings show that 93% were found to be authentic (shahih), 6% were unreliable (dla’if), and 1% were not judged because the researcher did not find them. These unreliable hadiths have authentic ahadith al-bab strengthening them in terms of meaning.